Carbon Footprint Generated By Egg Production. Case: Velasco Poultry Farming, Province Of Manabi, Ecuador (Revista Científica Ciencias Naturales y Ambientales, 2023)
The aim of this research was to estimate the carbon footprint generated by the production of eggs in the Velasco poultry farm, province of Manabí, coastal Ecuador. Through the application of the non-experimental quantitative method, a diagnosis of the farm under study was made and, subsequently, the greenhouse gas emissions generated from the productive activities developed in the Velasco Poultry Farm were quantified, multiplying the consumption of each activity by its emission factor. It was obtained that the farm emits 110.91 tons of CO2e per year, with the laying stage being the one with the highest percentage (74.57%), while feed production was the category with the highest contribution with 84.50%. In conclusion, the determination of the carbon footprint made it possible to identify the specific sources of greenhouse gas emissions, allowing to address specific problems to mitigate the emissions.
Keywords: Greenhouse gases; Poultry industry